The Effect of Dysminore Gymnastics on Menstrual Pain in Young Girls In Grades VII and VIII - Ade Marlisa Rahmadayanti; Titin Apriyani (Indonesian Journal of Global Health Research, 2025)
Dismenorrhea is pain in the pelvic region due to menstruation and the production of prostaglandins. Dismenorrheic exercise is a physical exercise activity that can relieve menstrual pain. During exercise, endorphins are produced in the body. Endhorpin acts as a natural sedative and can make you feel comfortable. This study aims to find out the effect of dysmenorrheic gymnastics on menstrual pain in teenage daughters. The research design used was a quasi-experiment with a two-group pre-test-post-test design and sampling using non probability Sampling method with a total sampler technique consisting of 30 students of classes VII and VIII in Bakti Mother 2 Palembang High School, samples were divided into two groups, 15 control groups and 15 intervention groups. The average menstrual pain in the intervention group was 4.60 and after exercise disminored 3.13, in the control group the average pre-test was 3.33 and after the post-test 3.20. Data analysis using the wilcoxon test showed that there was a significant value in the intervention group with a p-value of 0,000, whereas in the control group there was no significant value with the p- value of 0.157. It is expected that adolescents who experience menstrual pain will be able to deal with non-pharmacological treatments such as dysmenorrheic gymnastics, thereby reducing pain and the use of pharmacological drugs that have side effects.